2-[(Pyridin-3-ylamino)methyl]pheno1 - Xu, J.; Gao, S.; Ng, S.W. (International Union of Crystallography, 2011)
In the title compound, C(12)H(12)N(2)O, the aromatic rings at either ends of the -CH(2)-NH-link are twisted by 68.79 (7)degrees. In the crystal, the hydroxy substituent is a hydrogen-bond donor to the N atom of the pyridine ring of an adjacent molecule, and the hydrogen bond generates a chain along the b axis; it is also a hydrogen-bond acceptor to the amino group of another adjacent molecule. The two hydrogen bonds lead to the formation of a layer structure.